Frequency stability improvement for piezoresistive micromechanical oscillators via synchronization - Pu, Dong; Huan, Ronghua; Wei, Xueyong (AIP advances, 2017)
Synchronization phenomenon first discovered in Huygens’ clock shows that the rhythms of oscillating objects can be adjusted via an interaction. Here we show that the frequency stability of a piezoresistive micromechanical oscillator can be enhanced via synchronization. The micromechanical clamped-clamped beam oscillator is built up using the electrostatic driving and piezoresistive sensing technique and the synchronization phenomenon is observed after coupling it to an external oscillator. An enhancement of frequency stability is obtained in the synchronization state. The influences of the synchronizing perturbation intensity and frequency detuning applied on the oscillator are studied experimentally. A theoretical analysis of phase noise leads to an analytical formula for predicting Allan deviation of the frequency output of the piezoresistive oscillator, which successfully explains the experimental observations and the mechanism of frequency stability enhancement via synchronization.